The Relationship between Learning Motivation and Mathematical Communication Skills in Vocational High School Students - Nurwulandari, Astiani; Septian, Ari; Soeleman, Muhamad (PRISMA, 2025)
This study aims to analyze the relationship between learning motivation and mathematical communication skills in vocational high school students. The background of this study is the importance of mathematical communication in mathematics learning, as well as the low learning motivation of vocational high school students that impacts these abilities. The research method used is quantitative with a correlational approach. The population in this study were grade X students at SMK Negeri 1 Cipanas, with a sample of 26 students from grade X MPLB 3 selected using a purposive sampling technique. The instruments used included a learning motivation questionnaire and a mathematical communication ability essay test. The results showed that there was no positive and significant relationship between learning motivation and mathematical communication skills in vocational high school students. Based on these results, it can be interpreted that high learning motivation does not necessarily align with high mathematical communication skills. This means that even though students have a high learning drive, it does not automatically make them able to communicate mathematical ideas well. This finding implies that increasing learning motivation alone is not enough to improve students' mathematical communication skills. Mathematics learning needs to be designed not only to motivate students but also to specifically train mathematical communication skills such as explaining ideas, using symbols appropriately, and interpreting real-world situations into mathematical models.